2018
DOI: 10.1039/c8ra00306h
|View full text |Cite
|
Sign up to set email alerts
|

Azide–alkyne cycloaddition reactions in water via recyclable heterogeneous Cu catalysts: reverse phase silica gel and thermoresponsive hydrogels

Abstract: Azide–alkyne cycloaddition reactions were performed via copper catalysts immobilized onto two types of supports in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Additionally, in 2018, Lim et al [9] conducted a copper-catalyzed one-pot azide-alkyne cycloaddition reaction using two heterogenous Cu-reverse phase silica gel catalytic systems (Scheme 6).…”
Section: Silica Supported Copper Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, in 2018, Lim et al [9] conducted a copper-catalyzed one-pot azide-alkyne cycloaddition reaction using two heterogenous Cu-reverse phase silica gel catalytic systems (Scheme 6).…”
Section: Silica Supported Copper Catalystsmentioning
confidence: 99%
“…Through their heterogenous recyclable catalyst, they were able to carry out these reactions efficiently, in water and in short reaction times, and demonstrated their catalyst to be capable of recovery and reuse up to four cycles with no significant loss of activity, which was a leading development when compared to other similar studies. Additionally, in 2018, Lim et al [9] conducted a copper-catalyzed one-pot azide-alkyne cycloaddition reaction using two heterogenous Cu-reverse phase silica gel catalytic systems (Scheme 6). Scheme 6.…”
Section: Silica Supported Copper Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhee et al immobilized Cu(I) and Cu(II) species onto reversephased silica gel [25]. In this work, a 2-pyridinecarboxaldehyde ligand was attached on reversed-phase 3-aminopropylfunctionalized silica gel (APSi) in dichloromethane as a solvent.…”
Section: Reviewmentioning
confidence: 99%
“…260 The potential of multicomponent reactions for the preparation of 1H-1,2,3-triazole derivatives has become extremely useful in recent years to produce complex macromolecular structures 261 and several studies have reported the use of this strategy in the preparation of 1,4-disubstituted 1H-1,2,3-triazoles. [262][263][264][265][266][267]…”
Section: Scheme 25mentioning
confidence: 99%